ESRA19-0671 Re-stop before you re-block… an unusual case of wrong sided regional anesthesia. (30th August 2019) - Pascarella, G; Costa, F; Del Buono, R; Sebastiani, C; Longo, F; Gargano, F; Agrò, FE
Abstract : Background and aims: Wrong sided regional anesthesia is a serious and avoidable event and may be considered as a sentinel event in healthcare institutions. WHO developed a standard check list in order to prevent errors and adverse events in surgery. In November 2010, the Safe Anesthesia Liaison Group (SALG-NHS) started the 'STOP BEFORE YOU BLOCK' (SBYB) campaign in order to further reduce incidence of wrong side regional anesthesia. the campaign suggests verifying the side to be blocked immediately before needle insertion. We describe an unusual case of wrong sided block. Methods: A 51-year-old male patient was scheduled to undergo right knee endomodel prosthesis revision. the procedure duration was estimated to be 3 hours. After the WHO safety checklist and marking the surgical site, a right unilateral spinal anesthesia and an omolateral right adductor canal block were performed; deep propofol sedation was started. After 3 hours, the surgeon said he needed at least 2 more hours. In order to prolong a surgical anesthesia for the knee, the ultrasound machine was taken into the operating room and a left fascia iliaca block was performed under the surgical drapes. The day after the patient complained about a quadriceps weakness contralateral to the operated knee. Results: The patient and the surgeon were explained about the error and the unusual circumstances. An incident report was forwarded. the patient completely recovered his muscle strength. Since then, the 'SBYB' poster is hanging from our ultrasound machines. Conclusions: Even if we already stopped, thought and blocked, if we decide to reinforce our regional anesthesia, we need to re-stop, before to re-block.